Media Pembelajaran Powtoon untuk Meningkatkan Hasil Belajar Siswa Materi Keberagaman Budaya Berbasis Kearifan Lokal (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2025)
This study aims to develop powtoon learning media based on local wisdom on the subject of cultural diversity in Kediri to improve the learning outcomes of fourth grade students of SDN Sukoharjo. The problems underlying this study are the lack of use of learning media and teachers have not used technology-based learning media. This study uses the Research and Development (R&D) method, development studies type with formative testing according to Tessmer. With two steps, namely Preliminary and Prototyping. In preliminary there are two stages, namely analysis and design. While in prototyping there are five stages, namely selfevaluation, expert review, one to one, small group, field test. Product validation is carried out by expert material validators and media experts with an average percentage of 88%. The results of the trial through the one-to-one, small group, and field test stages show that the developed powtoon learning video is effective in improving student learning outcomes. This is indicated by an increase in the average value of learning outcomes from pre-test to post-test. Thus, learning videos are suitable for use as learning media to improve student learning outcomes on cultural diversity material.